A Quality Function Deployment (QFD) Approach in Determining the Employer's Selection Criteria. (8th September 2015) - Muda, Nora; Mat Roji, Noor Sulawati
Abstract : The industrial training program is part of the academic curriculum at the tertiary level. It plays an important role in providing students with the exposure to a real working environment in the industry. Through this program, the higher education institutions (HEI) could identify the gaps in the curriculum based on the requirements from the industry. In addition, the feedback from the industry will help the HEI to equip students with relevant skills according to the demands from the industry. Indirectly, it can help to address the issue of unemployed graduates of which the number seems to increase from time to time. Therefore, this study aims to obtain the feedback from the employers out there in order to determine the most preferred criteria in selecting students for the industrial training placement by using Quality Function Deployment (QFD) approach. The findings, through the development of house of quality based on the QFD approach, show that communication skills and students' participation in sports and cocurricular activities at their university are the most preferred selection criteria. Therefore, the QFD approach can be used to translate the employers' feedback in improving the marketability of the students in the industry.